Studying the Effect of the Energy Settings of the HO-YAG Laser and the Composition of the Stones on the Fragmentation Time in vitro - Ferial.Y. Nazal ,; Hussein Al Husseini ,; Hazim R.Akal , (University of Thi-Qar Journal of Science, 2021)
Among the many in vitro lithotripsy devices, a holmium-YAG laser lithotripter has been developed to treat urinary tract stones . This research aims to show the effect of the coefficients of the Ho-YAG laser at wavelength 2100 nm on the in vitro fragmentation time and stone composition by checking the stone formation and stabilization of the energy of the pulsed holmium laser while calculating the time required to break the stone . From March 2020 to October 2020, 50 ureteral stone samples were collected from 50 patients (as a result of lithotripsy surgery <10 mm) between the ages of 10-85 years . The patient was treated in the Urology department of Al-Hussein Teaching Hospital by using a Ho-YAG laser radiation wavelength of 2.12 µw, the reaction absorption coefficient 30 cm-1, with a maximum output power of 20 watts, for a laser pulse width of 350 microseconds in an optical fiber with a diameter of 272-550 microns with a power of 0.8 - 1.2 J at 6-8 Hz. The samples obtained are selected groups of stones recovered after lithotripsy. This study showed that the average size of the stones less than 10 mm was 9.5 ± 0.7 mm for the first group of stones of the same composition (calcium oxalate monohydrate), and the mean age of the patients was 31 ± 2.82 years and the time of fragmentation ( 70 ± 1.41) sec, with a pulse energy of 0.8 J with a repetition rate of 6 Hz.